AN ANALYSIS OF ILLOCUTIONARY ACT IN “HOW TO TRAIN YOUR DRAGON 2” MOVIE - Setiani, Anggita; Utami, Dewi Putri (IKIP Siliwangi, 2018)
This study deals with the types of illocutionary acts in “How to train your dragon 2” movie. The research concerns with illocutionary act produced by the main character in “How to train your dragon 2” movie. The aim of this research is to find out the illocutionary acts produce by the main character in the movie. This research applied descriptive qualitative method. There are 333 utterances and the percentages of data were 43.8% of representative, 41.7% of directive, 7.3% of expressive, 6.6% of commissive and 0.6% of declarative. The most dominant type of illocutionary acts found is representative. It shows that the main character tended to convey his utterance for describing states or events in the world that he believed it to be. This finding supported Cutting (2002:17) that representative are act in which the word said what the speaker affirm to be the case or not. It is because what Hiccup tended to say in the movie about statement of fact, assertion, conclusions and descriptions about things. Keywords: Speech act, Illocutionary act, Movie